2014
DOI: 10.1115/1.4027328
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alveolar Topology on Acinar Flows and Convective Mixing

Abstract: Due to experimental challenges, computational simulations are often sought to quantify inhaled aerosol transport in the pulmonary acinus. Commonly, these are performed using generic alveolar topologies, including spheres, toroids, and polyhedra, to mimic the complex acinar morphology. Yet, local acinar flows and ensuing particle transport are anticipated to be influenced by the specific morphological structures. We have assessed a range of acinar models under self-similar breathing conditions with respect to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 67 publications
(165 reference statements)
1
48
0
Order By: Relevance
“…They also indicated that the exact shape of alveoli may have less influence on the presence of alveolar recirculation. Many other works have also shown this convective mixing effect both qualitatively and quantitatively . Hofemeir and Sznitman showed that alveolar geometric topology influences localized flow characteristics and deposition sites for finer particles.…”
Section: Image‐based Computational Fluid Dynamics Of Airflow In the Amentioning
confidence: 77%
See 2 more Smart Citations
“…They also indicated that the exact shape of alveoli may have less influence on the presence of alveolar recirculation. Many other works have also shown this convective mixing effect both qualitatively and quantitatively . Hofemeir and Sznitman showed that alveolar geometric topology influences localized flow characteristics and deposition sites for finer particles.…”
Section: Image‐based Computational Fluid Dynamics Of Airflow In the Amentioning
confidence: 77%
“…Nevertheless, understanding of airflow mechanics and particle transport in the acinar region has significantly advanced due to CFD. One important question that has been investigated is the role of proximal and distal acinar airways as mixing chambers . Existence of mixing in these submillimeter alveolar units has applications in both pharmacological and clinical sectors.…”
Section: Image‐based Computational Fluid Dynamics Of Airflow In the Amentioning
confidence: 99%
See 1 more Smart Citation
“…3(b) and 3(c)); this latter flow characteristic is a well-known property of low-Re separated cavity flow phenomena 34,41,53,54 and has been previously shown in the context of adult air-filled lungs both experimentally 41,55,56 and numerically. 33,51,57,58 To deliver a comprehensive rendering of the different flow regimes anticipated across the developmental stages of fetal lungs, our numerical and experimental flow results are summarized in the phase map of Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…A constant pressure of 100 000 Pa was arbitrarily set at the domain outlet. 33,50,51 Mesh refinement studies were performed to ensure that flow solutions were grid independent where changes in the average flow velocity magnitude and average shear rate over the alveolar cavity opening were within 1% upon further mesh refinement, as previously established. 41 All numerical solutions were found to converge with residuals below 10 À7 , measuring the imbalance in conservation of mass.…”
Section: F Computational Fluid Dynamicsmentioning
confidence: 99%